Socio-Structural factors related to young people seeking HIV/AIDS testing: An integrative review (Research, Society and Development, 2021)
Objective: To investigate in the literature the socio-structural factors present in the lives of 15- to 24-year-olds who seek a health service to perform the HIV/AIDS serological test. Methodology: This is an Integrative Literature Review (RIL) study with a qualitative approach, delimited by the research question: What are the socio-structural factors that influence young people aged 15 to 24 years to seek a health service to perform the test? HIV/AIDS serology ?. Health Sciences databases were used: PUBMED (United States National Library of Medicine), BDENF (Nursing Database), LILACS (Latin American and Caribbean Literature in Health Sciences) and MEDLINE (Medical Literature Analysis and Retrieval System Online). After adding filters and using inclusion and exclusion factors, a sample of 30 articles was obtained, which were categorized according to the MSEM. Results and Discussion: The most cited factors were: low education level, age group, economic insecurity, unstable housing, family conflicts and transactional sex. Also highlighted were the relationships that show vulnerability, such as sexual violence, marginalization, social exclusion, gender issues, social support, and family and other social groups. Final considerations: Finally, the socio-structural factors that lead young people from 15 to 24 years of age to seek an HIV/AIDS testing service, permeate individual, community, and even political issues, thus involving the entire social sphere in which they young people are inserted.